Single-Electron Transport and Detection of Graphene Quantum Dots - Xinxing Li; Jinggao Sui; Jingyue Fang (Nanomaterials, 2023)
The integrated structure of graphene single-electron transistor and nanostrip electrometer was prepared using the semiconductor fabrication process. Through the electrical performance test of the large sample number, qualified devices were selected from low-yield samples, which exhibited an obvious Coulomb blockade effect. The results show that the device can deplete the electrons in the quantum dot structure at low temperatures, thus, accurately controlling the number of electrons captured by the quantum dot. At the same time, the nanostrip electrometer coupled with the quantum dot can be used to detect the quantum dot signal, that is, the change in the number of electrons in the quantum dot, because of its quantized conductivity characteristics.